GIS to boost horticultural production - Parthasarathy, Utpala; Jayarajan, K (Indian Horticulture, 2019)
The GIS is a transverse information system that helps the farmers by: instantaneously locating of plots for cultivation, performing of comparative studies of the plots in a specific area, based on their variety, year of planting or condition. All sectors in horticultural enterprise can use GIS technology to share data, increase yields, predict outcomes, and improve business practices. By applying GIS technology, the field operations can be effectively managed, saving resources and efficiently managing the enterprise. The use of interactive maps, developed using GIS tools can prepare information-dense reports which can give a unique perspective to the operations. The powerful analytical capabilities of GIS offer an array of options for visualizing farming conditions, as well as measuring and monitoring the effects of farm management practices and to support management decisions.